Exploring Community Resilience: The Joint Roles of Environmental Knowledge and Risk Perception in Pro-Environmental Behavior - Yu Zhang; Zihao Dong; Yanying Mao; Xiaosen Huo; Liu Wu (Buildings)
Promoting pro-environmental behaviors among individuals in the community is crucial to increase community resilience and to address environmental challenges. However, a persistent intention–behavior gap often exists, particularly in separate private or public spheres. Historically, addressing this gap has involved focusing on single moderating variables such as environmental knowledge or environmental risk perception. Yet, few studies have examined it in both spheres under the combined moderating influence of two variables. Our research plans to bridge this gap by exploring pro-environmental behaviors in the private and public spheres using conditional process models under the joint moderating effects of EK and environmental risk perception. Our findings reveal a larger intention–behavior gap in the public sphere compared to the private sphere, which highlights the greater challenges in translating environmental intentions into collective actions within the community. In private sphere behaviors, we observe the most significant positive moderating effect on intention–behavior alignment when individuals possess high environmental knowledge coupled with low environmental risk perception. This combination facilitates the bridging of the intention–behavior gap, fostering individual actions that can contribute to community resilience. Conversely, in public sphere behaviors, optimal alignment occurs when both environmental knowledge and risk perception are high, facilitating the translation of intentions into actions. These insights offer targeted policy recommendations for governments and policymakers, contributing to a deeper understanding of increasing community resilience.